ANALISIS PENGARUH KOMPENSASI, GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN UD. SURYA MANALAGI KEDIRI - Heru Sutapa; Slamet Riadi; Bondan Subagyo (BEMJ : Business, Entrepreneurship, and Management Journal, 2023)
The research that the researchers took was related to compensation, leadership style, and motivation for performance at UD. Surya Manalagi Kediri. This study aims to know and explain about compensation, motivational leadership style for employee performance at UD. Surya Manalagi Kediri. Descriptive Quantitative is a method that researchers use. Employees at UD. Surya Manalagi Kediri as the object that the researchers took. The data processing that researchers use includes validity tests, reliability tests, classical assumption tests, hypothesis tests through t tests, multiple linear regression analysis, and coefficients of determination. The results obtained are a positive and relevant influence on compensation on employee performance which is shown by a sig value of 0.045<0.05, leadership style has a positive influence on teacher performance shown a sig value of 0.00 < 0.05, motivation has a significant positive effect on UD employee performance. Surya Manalagi Kediri is indicated with a sig value of 0.001<0.05. Keywords: compensation, leadership style, motivation, employee performance